HANS OF THE OTTOMAN PERIOD: AN ANALYSIS OF THE SPATIAL CONCEPT IN FUNCTION OF A MODERN TURIST PURPOSE - Namicev, Petar (Journal of process management and new technologies, 2017)
The highest developed form of a spatial concept of ainn in the urban area of ​​the Ottoman period is the rectangular form of the spatial organization of the hans from the 15th and the 16th centuries. The most important examples are Kurshumlihan, Sulihan and Kapan han in the old bazaar in Skopje, which are part of a complex spatial system of the historical part of the city. According to the urban concept of the Ottoman builders, a group of public buildings has been formed, where mosque, bedesten, hamam, etc. appear beside another. Spatial analysis of auxiliary rooms and overnight accommodation, or open spaces (atrium, porch) has a certain specific ratio. The experience of the organization from historical buildings is a valuable experience in terms of balancing different contents of the used space, its purpose and adjustment to the current needs of the object. The experiences from the study of certain spatial elements of the hans and from the analysis of the current tourism development in which they are included, can be applied in the concept of modern tourist objects.